Statutory regulation of forced sale of the home in South Africa - Steyn, Lienne (University of Pretoria, 2012)
The home of a debtor has never enjoyed specific statutory protection against forced sale in the individual debt enforcement and insolvency procedures in South Africa. In Jaftha v Schoeman and Others; Van Rooyen v Stoltz and Others (2005 (2) SA 140 (CC)) and Gundwana v Steko Development CC and Others (2011 (3) SA 608 (CC)), the Constitutional Court recognised that in the individual debt enforcement process execution against a debtor's home, even where it has been mortgaged in favour of a creditor, may constitute an unjustifiable infringement of the right to have access to adequate housing, provided by section 26 of the Constitution. The effect of these decisions is that, in every case in which a creditor seeks to execute against a person's home, a court must consider "all the relevant circumstances" to determine whether execution is justifiable, in terms of section 36 of the Constitution. The absence of a properly constructed framework, incorporating clear substantive and procedural requirements, within which these recently established principles must be applied, has led to divergent approaches in the courts and a lack of clarity regarding circumstances in which execution against a debtor's home will be permitted. Further, courts have not considered the impact of section 26 and other rights on the position where a debtor's home is realised by the trustee of an insolvent estate in terms of the Insolvency Act 24 of 1936. This has given rise to a number of unanswered questions as well as to a lack of predictability that potentially hold adverse consequences for bond finance, commerce, and the economy generally. The need to balance the competing interests emphasises the necessity for a coherent contextual framework within which forced sale of a debtor's home may occur. This thesis examines issues surrounding forced sale of a debtor's home in South Africa. It compares the position in other legal systems and suggests mechanisms and an appropriate method, or process, for inclusion in statutory provisions to regulate the forced sale of a debtor's home in both the individual debt enforcement and insolvency procedures in South Africa.
Keywords: Forced sale; Vente forcée

The legal and institutional framework for the enforcement of online consumer arbitration awards: evidence from Australia and Sri Lanka - Kananke, Chinthaka Liyanage (La Trobe University, 2012)
Keywords: Australia; Commercial law; Conflict of laws; Consumer protection; Dispute resolution; Electronic commerce; Sri Lanka

Disability, discrimination and equal opportunities : a comparative labour law study - Harmse-Truter, Laurentia (University of Johannesburg, 2012)
This study aims to investigate the different ways in which the position of people with disabilities can be addressed. Antidiscrimination legislation can play a very important role. Efforts to create equal opportunities must, however, not be limited to legislative initiatives and policy declarations. There is an urgent need for education and training of this minority group. 7 Systematic efforts to heighten public awareness of civil rights and in particular the recognition of the rights of the disabled community are imperative. This study aims to bring home the truth that "disability rights are an idea and ideal whose time has come. ,, When addressing the issue of disability discrimination (or for that matter any kind of discrimination) several principles need to be addressed, the most important being the following: The meaning of the concept of "equality" needs to be established. The fact that all people are equal, does not necessarily mean that all people must be treated the same. When speaking about disability discrimination one must know who forms part of the protected class. For that reason the first issue that must be addressed is the definition of "disability": This leads to the next question, namely which individuals should be protected by anti-discrimination laws and should they benefit from affirmative action measures? What is meant by the term "discrimination"? Is it at all permissible to distinguish between groups of people and, if so, when and which standards are to be applied? What role can anti-discrimination legislation fulfil in the struggle for equality? When dealing with anti-discrimination legislation, what is required in order to prove discrimination and what remedies must be available to an aggrieved party? Normally, in case of criminal action proof is required beyond reasonable doubt and in case of civil action on the balance of probabilities. 10 Civil action offers more effective remedies, but should it be punitive in nature (by awarding damages to the aggrieved party) or non-punitive (by putting the aggrieved party in his/her "rightful place")? What sort of enforcement mechanism is needed? Is it a task for the ordinary tribunals or rather a special body created for that purpose? What defences should be available to an employer accused of discriminatory practices? Who should benefit from enforcement? Only the individual victim or all members of that group? Is anti-discrimination legislation sufficient or is something in addition called for? If positive measures are required, what form must these measures take? This study will address these questions specifically with relation to people with disabilities.The "equality principle" will first be studied. Thereafter the concept of "disability" will be defined. There is a movement away from a medical model of disability towards a social model that takes account of the disabling effects of attitudes and structural barriers on the position of disabled people. Then the concept of "discrimination" will be addressed. Discrimination has many different forms and can take place in different contexts In the following chapter possible solutions to the problem of disability discrimination will be raised. Thereafter follows an important comparative analysis of different jurisdictions on international, supra-national and national level. Different jurisdictions have reached different stages in addressing this problem. The factual analysis of each jurisdiction will include the existence of any anti-discrimination legislative measures, the scope of the protected class, applicable employment provisions, defences available to employers, and the success achieved in addressing the problem. The contentious issue of affirmative action measures will also be addressed. By drawing inferences from the comparative study, suggestions will be made for future developments in South Africa. The conclusion is reached that it is imperative for South Africa to draft disability anti-discrimination legislation that takes account of the needs of this minority group. Legislative initiatives, however, are not enough and must be supported by various programmes aimed at the disabled themselves and the community that they live in. Only then can human rights become a reality also for people with disabilities.
Keywords: Comparative law; Discrimination; Employment; Labour law; People with disabilities

The legal implications of harmonising labour laws in the Southern African Development Community (SADC) region - Okharedia, Akhabue Anthony (University of South Africa, 2012)
The purpose of this research is to explore the need for, and the legal implications of, harmonising labour laws in the Southern African Development Community (SADC). Chapter One highlights a number of factors that call for the harmonisation of labour laws in the SADC region and discusses some of the reasons why labour laws are not well developed in the region. The influence of globalisation on labour standards in southern Africa and the influence of regionalism on the harmonisation of labour laws are discussed at length. The inference that could be drawn from this discussion is that for a regionalisation process in southern Africa to be successful, there is an urgent need to harmonise the region’s labour law system. This thesis confirms that Southern Africa has many lessons to learn from the regional harmonisation of labour law in the European Economic Community and the current European Union. The implementation of international labour standards in southern Africa is investigated. The main areas examined include (1) freedom of association, (2) collective bargaining, (3) forced labour and (4) discrimination. The findings of this investigation show that there is no uniformity in the implementation of International Labour Organisation (ILO) standards in the SADC region and, therefore, it is recommended labour law should be harmonised in terms of ILO standards. In respect of the benefits to be derived from the harmonisation process, an empirical investigation was conducted in the SADC region and the following is recommended: the harmonisation of labour law in the SADC region will help with the implementation of ILO standards, protection of workers against the economic power of employers in the workplace and maintaining similar benefits for migrants in the region.
Keywords: Child labor; Collective bargaining; Compulsory labour; Discrimination in employment; Discrimination in the work environment; Droit du travail; Forced labour; Freedom of association; Harmonisation; International Labour Organization; International Labour Standards; Labour law; SADC

A proposal to guide future draft article provisions for a model harmonised international commercial arbitration law code (HICALC) in the Middle East and North Africa or a uniform Arab arbitration law - Ayad, Mary Boulos (Macquarie University, 2012)
MENA law codes are a well-crafted blend of civil and Islamic law in which civil law principles do not contravene with Islamic provisions. They were originally based on Sanhuri’s codes to varying degrees. Yet, common law principles derived either from English common law or Islamic customary usages are unidentified and thus ignored. Here, this lacuna is rectified through a comparative analysis of the primary data (eg, cases, statutes and arbitral award decisions), adding common law and uncodified Islamic custom to MENA law codes. The purpose of this comparative analysis is to allow common legal principles found at civil, common and Islamic law to be distilled in the service of creating a new harmonised international commercial arbitration law code (HICALC) or uniform Arab arbitration law (UAAL) for adoption in the MENA.1 These principles already form part or all of the legal systems in the MENA. They can be readily assimilated into a harmonised or uniform code. Would this new harmonised code lead to higher arbitral award enforcement in the MENA? According to the evidence the answer is yes. The author understands that at the present time the HICALC articles are ambitious and as such they are a beginning point and can initially be taken as a harmonised international commercial arbitration common rule (HICACR). A brief overview of the history of harmonisation is given. An assessment of the status of the laws and traditions of the MENA was carried out. A comparative analysis of the relevant differences and similarities of the case study countries (Egypt and the United Arab Emirates) was carried out to show the gaps in the laws and areas requiring reform. An analysis of enforcement of arbitral awards was carried out. The unique problems that ICA and IIA encounter in the MENA as derived from an analysis of cases and the laws therein are expounded in consideration of matters pertaining to enforcement. A comparative analysis of universal principles which must be included in a new code, including custom, was carried out. An analysis of the unique features and unique needs of the MENA was carried out in order to inform the Draft Article Provisions. An analysis of important international legal instruments dealing specifically with international arbitration and the gaps therein is given. The draft articles for a HICALC or uniform Arab arbitration law were derived as a result of these multiple layers of analysis. The matters of compétence de la compétence, expropriation, interest, public policy and sovereign immunity are highlighted as the most important areas requiring urgent reform. The results of this research are suggested Draft Article Provisions for a model Harmonised International Commercial Arbitration Law Code (HICALC) or a uniform Arab arbitration law. Future drafters may refer to and revise these articles for implementation. The synthesis of theory and practice addresses doctrinal matters that arise in international investment arbitrations and international commercial arbitration, with a focus on investor–State arbitrations. This synthesis provides a new theoretical conception of the jurisprudence of international arbitration, particularly in regard to the matters of res iudicata, precedent and expansion of arbitral tribunal powers and jurisdiction.
Keywords: Arab countries; Arbitrage; Arbitragem; Arbitration; Arbitration Law; Arbitration and award; Commercial law; Commercial law (Islamic law); Common rule; Dispute resolution; HICACR; HICALC; Harmonised International Commercial Arbitration; International commercial arbitration; MENA law codes; Middle East; North Africa; UAAL; Uniform Arab arbitration law

Financial liberalisation and economic growth in ECOWAS countries - Owusu, Erasmus Larbi (University of South Africa, 2012)
The thesis examines the comprehensive relationship between all aspects of financial liberalisation and economic growth in three countries from the Economic Community of West African States (ECOWAS). Employing ARDL bounds test approach and real GDP per capita as growth indicator; the thesis finds support in favour of the McKinnon-Shaw hypothesis but also finds that the increases in the subsequent savings and investments have not been transmitted into economic growth in two of the studied countries. Moreover, the thesis also finds that stock market developments have negligible or negative impact on economic growth in two of the selected countries. The thesis concludes that in most cases, it is not financial liberalisation polices that affect economic growth in the selected ECOWAS countries, but rather increase in the productivity of labour, increase in the credit to the private sector, increase in foreign direct investments, increase in the capital stock and increase in government expenditure contrary to expectations. Interestingly, the thesis also finds that export has only negative effect on economic growth in all the selected ECOWAS countries. The thesis therefore, recommends that long-term export diversification programmes be implemented in the ECOWAS regions whilst further investigation is carried on the issue.
Keywords: ARDL-Bounds testing approach; Capital accounts liberalisation; Co-integration; ECOWAS; Economic Community of West African States; Economic growth; Economic stablization; Financial crises; Financial liberalisation; Ghana; Interest rates liberalisation; Ivory Coast; Monetary Policy; Nigeria; Stock market developments

Board Structure, Ownership Concentration and Intellectual Capital - Zhang, Meiyi (Victoria University of Wellington, 2012)
This thesis investigates the influence of board structure and ownership concentration on the level and value relevance of intellectual capital disclosure. This thesis is motivated by the limited post-IFRSs (International Financial Reporting Standards) adoption intellectual capital disclosure studies carried out in a less stringent regulatory environment of New Zealand, and limited research addressing the determinants of the level and value relevance of intellectual capital disclosure. Based on an application of agency theory, cost-benefit theory and value relevance approach, this thesis argues that firm-specific factors are expected to have a significant impact on the level and value relevance of intellectual capital disclosure. Within the agency theory, board structure and ownership concentration mitigate agency costs by enhancing the monitoring function of the board over managers’ opportunistic behaviour, which consequently influence the level of intellectual capital disclosure. In addition, as New Zealand has less tough rules in relation to board structure and ownership concentration, it is expected that these relationships will be more easily identified in the New Zealand context. Second, as most of the intellectual capital disclosure is voluntary, this disclosure is subject to a firm’s cost-benefit analysis. Cost-benefit theory suggests that a firm should not fully disclose its information unless the benefits outweigh the costs of the disclosure. Therefore, the level of intellectual capital disclosure is also influenced by the factors that determine the costs and benefits of the disclosure. Finally, this thesis adopts the value relevance approach to measure the quality of the disclosure. It is expected that the factorsassociated with the level of the disclosure also influence the value relevance of the intellectual capital disclosure. This thesis is based on a sample of 155 firms listed on the New Zealand Exchange covering a total of 519 firm-years over the period between 1 January 2008 and 31 August 2011. A self-developed disclosure index and multiple regression analysis are employed to test the hypothesised relationships. Overall, the results indicate that the average level of intellectual capital disclosed by New Zealand listed firms is low and the human capital component is the most frequently disclosed intellectual capital component. The results provide strong evidence that board structure characteristics, including board size and independence, have a significant positive impact on the level of intellectual capital disclosure. There is strong evidence for a non-linear relationship between ownership concentration and the level of intellectual capital disclosure, which is robust to various types of intellectual capital (i.e. human, relational and structural capital). The results show marginal evidence that board gender diversity has a positive impact on the level of intellectual capital disclosure. In terms of the value relevance of intellectual capital disclosure, only board size has a positive impact on the value relevance of the intellectual capital disclosure. In the individual component analysis, board independence is found to have a significant positive impact on the value relevance of the human and relational capital disclosures. This thesis provides the most recent evidence on the influence of board structure and ownership concentration on the level and value relevance of intellectual capital disclosure in a less stringent regulatory environment of New Zealand. These findings have important implications to regulators, and assist information users in the interpretation of the voluntary intellectual capital disclosure.

Lex mercatoria in international arbitration theory and practice. Vol 1 - Elcin, Mert (European University Institute, 2012)
This dissertation suggests a new theory of lex mercatoria that takes into account the complex and spontaneous order of international commerce. Since the emphasis is put on the nature of this order, the concept of lex mercatoria is examined as an ex post governance mechanism resolving contractual disputes with a view to maintaining and restoring the order of international commerce, without focusing on the traditional distinction of the doctrine between national and non-national legal rules applicable to the substance of such disputes in explaining the concept. The aim is to reflect lex mercatoria’s subtle effect on the practice of international arbitration, and to provide an explanation of lex mercatoria as a solution to the problems of the institution of international arbitration in terms of uncertainty and unpredictability of awards, rather than representing it as a factor aggravating those problems. Lex mercatoria is defined as the law of adjudication of the disputes arising from international commercial contracts on the basis of a few substantive and procedural principles, under which the reasonable expectations of the parties to a particular contract become the single source of their contractual rights, obligations and risk allocations. The argument is that lex mercatoria can be applied to both the choice of law analyses and the substance of the disputes in international arbitration. In choice of law analyses, lex mercatoria addresses specific difficulties relating to the conflict of laws through a principled decision making, such as the applicable conflict rules, and the interpretation of the parties’ intentions as to the applicable substantive rules. In its substantive application, lex mercatoria deals with, either as lex contractus or as lex fori, the interpretation, supplementation and correction of the contract as well as the applicable national laws in accordance with the basic principles, on which the order of international commerce rests.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration and award; Commercial law; Conflict of laws; Foreign trade regulation; Law merchant

Lex mercatoria in international arbitration theory and practice. Vol 2 - Elcin, Mert (European University Institute, 2012)
This dissertation suggests a new theory of lex mercatoria that takes into account the complex and spontaneous order of international commerce. Since the emphasis is put on the nature of this order, the concept of lex mercatoria is examined as an ex post governance mechanism resolving contractual disputes with a view to maintaining and restoring the order of international commerce, without focusing on the traditional distinction of the doctrine between national and non-national legal rules applicable to the substance of such disputes in explaining the concept. The aim is to reflect lex mercatoria’s subtle effect on the practice of international arbitration, and to provide an explanation of lex mercatoria as a solution to the problems of the institution of international arbitration in terms of uncertainty and unpredictability of awards, rather than representing it as a factor aggravating those problems. Lex mercatoria is defined as the law of adjudication of the disputes arising from international commercial contracts on the basis of a few substantive and procedural principles, under which the reasonable expectations of the parties to a particular contract become the single source of their contractual rights, obligations and risk allocations. The argument is that lex mercatoria can be applied to both the choice of law analyses and the substance of the disputes in international arbitration. In choice of law analyses, lex mercatoria addresses specific difficulties relating to the conflict of laws through a principled decision making, such as the applicable conflict rules, and the interpretation of the parties’ intentions as to the applicable substantive rules. In its substantive application, lex mercatoria deals with, either as lex contractus or as lex fori, the interpretation, supplementation and correction of the contract as well as the applicable national laws in accordance with the basic principles, on which the order of international commerce rests.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration and award; Commercial law; Conflict of laws; Foreign trade regulation; Law merchant

Innovation and Intellectual Property: Strategic IP Management and Economics of Technology - Holgersson, Marcus (Chalmers University of Technology, 2012)
Innovations and technological developments have been recognized for their central importance for economic success and growth at least since the 1930s. Intellectual property (IP) and intellectual property rights (IPRs), such as patents, trade secret rights, and copyrights, have during more recent decades caught increasing attention, and, mainly due to various developments at macro level, IP has become an important source of competitive advantage at micro level in many industries. This has led to an increased importance of strategic IP management, and the related research field has been growing since the late 1990s. This thesis aims to contribute to this growing field, and the first purpose of this thesis is to explore and explain strategic and innovation related IP management practices, and the managerial and economic consequences of such practices. Apart from the growing importance of IP management in general, an increased focus on open and collaborative approaches for creating innovations has led to a need for new and adapted IP management skills. The second purpose of this thesis is therefore to develop managerial and economic frameworks, models, and tools to be used in the intersection between IP management and open innovation practices. These purposes are addressed in a cover paper and six appended research papers of theoretical/conceptual as well as of empirical nature, being based on interviews, questionnaires, patent statistics, and document studies. In connection to the first purpose the results show that, while many small firms have problems with properly benefitting from the patent system, large firms have increasingly developed their IP strategies, especially their patent strategies. The purpose is then not only to appropriate monopolistic returns from innovations but also to govern various forms of open innovation. Large firms were found to in a first step increase their patenting (in terms of quantity), and in a second step focus more on selective, quality-oriented, and internationalized patenting. Additional results show that the internationalization leads to a convergence in managerial choices of output markets for patenting worldwide, in parallel with market and technology diversification. Further, a case from mobile telecommunications illustrates the role of IP management in the governance of open innovation systems. Finally, two cases from the automotive industry illustrate the IP-related problems that arise in connection to divestments and other types of disintegrations (‘IP disassembly problems’), and how IP management can mitigate them. This leads to the second purpose, related to the development of models, tools, and frameworks for IP management in relation to open innovation. First, the thesis provides a conceptual framework of innovation openness, especially pinpointing the role of IPRs. This framework emphasizes three key dimensions of innovation openness: resource distribution, technology governance, and technology accessibility. Second, a framework for managing the IP disassembly problem is presented, enabling increased exit opportunities and decreased transaction costs. Third, a method for determining fair, reasonable, and non-discriminatory royalties in licensing collaborations is developed, applicable to multilateral licensing deals. It stands clear that contemporary IP management is not (and has never been) only about maximizing excludability. Strategic IP management must therefore be developed and integrated with technology and corporate management in order to foster success at the micro level of firms, and thereby also at macro level. Developments in IP management skills (e.g., sourcing, control, commercialization, licensing, valuation, pricing) and IP contracts will then most likely lead to increased efficiency of interorganizational technological relationships and quasi-integrated organizational forms, and thereby also to increased innovativeness and economic development.
Keywords: Adresse IP; Economie numérique; Intellectual property; Propriedade intelectual; Propriété intellectuelle

Effectiveness of the Beneficial Ownership Test in Conduit Company Cases - Jain, Saurabh (Victoria University of Wellington, 2012)
Countries enter into double tax agreements with the economic objective of preventing double taxation of cross-border transactions. To achieve this objective, the contracting states agree reciprocally to restrict their substantive tax law. That is, a major policy of double tax agreements is to reduce double taxation of residents of states that are parties to the agreement. Residents of third states sometimes contrive to obtain treaty benefits typically by interposing a person or a conduit entity in one of the contracting states. In order to ensure that a resident of a contracting state who claims treaty benefits is entitled to them in substance, double tax agreements should be interpreted according to their substantive economic effect. Generally, double tax agreements follow the pattern of the OECD Model Tax Convention. The OECD Model Convention addresses the double taxation of dividends, interest and royalties, commonly collectively known as "passive income", in Articles 10, 11 and 12 respectively. These provisions usually operate by reducing withholding tax imposed by a source state on passive income that flows from the source state to a resident state. In order to prevent a resident of a third state from obtaining a source state withholding tax reduction by interposing a person or a conduit entity in the resident state, the OECD Model Convention requires the immediate recipient of passive income to be the "beneficial owner" of that income. That is, the OECD Model Convention requires the immediate recipient to be an owner in a substantive economic sense. Courts and commentators have difficulty in interpreting and applying the concept of beneficial ownership to conduit entities that are corporations, commonly referred to as "conduit companies". They have attributed the cause of the difficulty to the absence of a definition of the term "beneficial owner" in the OECD Model Convention. This thesis argues that the difficulty in applying the beneficial ownership concept to conduit companies has arisen not because of the absence of the meaning of the concept, but because logically and from an economic perspective the concept cannot be applied to companies in general, not to conduit companies in particular. The beneficial ownership test was meant to be a test of economic substance. From an economic perspective, the benefit or the burden of a contract entered by a company is economically enjoyed or borne by its shareholders. That is, in substance a company cannot be considered as owning income beneficially. From this consideration, it follows that conduit companies can never be considered entitled to treaty benefits. Nevertheless, the OECD Model Convention applies the beneficial ownership test to conduit companies pursuant to an assumption that at least in some cases conduit companies can be the beneficial owners of passive income. The Model Convention's assumption is based on the legal perspective that courts conventionally adopt. According to this legal perspective, companies hold income beneficially because they exist as separate legal entities from their shareholders. Courts find themselves battling these opposing perspectives when applying the beneficial ownership test to conduit companies. In order to make income tax law work efficiently, courts that are obliged to determine whether to honour claims to treaty benefits made by conduit companies have preferred to employ the legal perspective. Courts have justified this approach by adopting surrogate tests for the actual beneficial ownership test. Most of the surrogate tests do not relate to the concept of ownership at all. This thesis categorises the surrogate tests as "substantive business activity" and "dominion". By analysing reported cases, the thesis identifies deficiencies in these tests. One of the proposed outcomes of the thesis is to suggest an alternative approach for deciding conduit company cases. The thesis suggests that courts should consider an arrangement as a whole and investigate reasons for the existence of an immediate recipient of passive income in the specific corporate structure. The thesis also recommends amendments in the official commentary on Articles 10, 11 and 12 of the OECD Model convention in order to address the conceptual shortcomings inherent in those Articles.
Keywords: Double taxation; OECD Model Tax Convention; Tax law

Full protection and security in International Law - Magnusson, Finnur (Universität Wien, 2012)
The thesis covers one of the investment standards of international investment law, namely the full protection and security standard. In Part I, the study is introduced in terms of structure and substance. Chapter 1 provides a description of the scope of the research topic and a definition of its terms and structure. Chapter 2 covers the historical development of the full protection and security standard. Part II deals with three fundamental issues concerning the standard: sources, interpretation and content. Chapter 3 contains a discussion dealing with the various sources of the standard. Each source will be studied independently. Chapter 4 will address general issues with regard to interpretation, such as to what extent the Vienna Convention on the Law of Treaties influences the process of interpretation. Chapter 5 deals with the content of the standard of full protection and security, including conceptual issues relating to the substantive elements of which the standard consists. Moreover, the chapter will ask questions as to which underlying issues are needed to explore when a due diligence assessment is made in order to determine whether a state has fulfilled its obligations to provide protection and security. Part III deals with issues relating to the violations of the standard. In Chapter 6, the violations of the standard and their many manifestations will be analyzed. The chapter will address whether certain fact-based scenarios can be established in which the standard is most commonly violated. Finally, Chapter 7 contains a summary of findings.
Keywords: Arbitral Awards; Bilateral Investment Treaties (BITs); Due diligence; Full protection standard; Full security standard; ICSID; International Investment Law; International law; Investment standards; Investments

Legal challenges of cross-border insolvencies in sub-saharan Africa with reference to Tanzania and Kenya: a framework for legislation and policies - Masoud, Benhajj Shaaban (Nottingham Trent University, 2012)
Although a substantial body of literature has developed in recent years in the area of cross-border insolvency, this scholarship has been dominated by scholars from the United States and Europe, so that a perspective from most of Sub-Saharan African (SSA) countries is lacking. This study addresses this perspective. It makes an in-depth examination and discussion of the challenges that SSA countries face in reform and application of cross-border insolvency law given the ever-growing multinational trade and investment. The study focuses on the risk of failure of SSA legislative processes to properly address the potential challenges of cross-border insolvencies in a manner that is sensitive to the local contexts and which provides a balance with international insolvency benchmarks. It examines cross-border insolvency theories; the global drivers for convergence of insolvency law through global insolvency norms; and the implications for cross-border insolvency regulations arising from cross-border trade and investment arrangements, such as the bilateral investment treaties, before considering the state and future of the legislative frameworks of SSA countries.
Keywords: Cross-border Insolvency; Insolvency; International insolvency

The Business Trust and its role as an entity in the financial environment - Nel, Ebenhaéser Cornelis (Nelson Mandela Metropolitan University, 2012)
The trust figure in South Africa has undergone an interesting process of evolution during the last century – from a mere gratuity or private tax evasion tool to a proper family protection, business entity, investment, and structured finance vehicle. Its flexibility and multi-functionality positioned the trust as an ideal legal institution for many innovative ideas in the search for holistic business structures, economic empowerment transactions, general estate planning and risk protection initiatives, and ultimately, its application as financial instrument and structured finance entity. The development of both traditional and synthetic securitisation schemes in South Africa has been investigated, with some emphasis on the application of the special purpose institution, which may be in trust form. It is submitted that the application of the trust figure has developed without any significant contribution from the local legislator. A sound legal and regulatory framework is crucial for the creation of a strong future environment for legal and financial vehicles. The question is, however, whether the current South African legal framework for the application of the business trust, and also as a vehicle for financial instruments, is adequately sound and robust in light of the standards set in the international business and financial environment. It is submitted that the hybrid nature of the South African legal landscape is conducive for the development of sound legal systems in an ever-changing legal and economic reality. It is further submitted that in the development of proper legal frameworks, South Africa should position itself particularly in its context as a Southern African developing democracy. The South African trust development is compared with that of some foreign jurisdictions as well as with international conventions and treaties of relevance. Some recommendations for necessary changes are made and it is submitted that such future development of the trust figure should not take place haphazardly, but within the context of a structured regulatory model
Keywords: Asset-backed financing; Corporations; Taxation; Trusts and trustees

A legal analysis of the application of articles I and III of the GATT 1994 on the economic development of ECOWAS member states - Ogbonna, Joseph Ifeanyichukwu (Brunel University, 2012)
This dissertation examines the tension inherent in the relationship between the Economic Community of West African States (ECOWAS) as Member States Parties of the GATT/WTO and the GATT/WTO regime. It focuses specifically on the tension triggered off by the requirements of Article I – the Most-Favoured-Nation principle (MFN) and Article III – the National Treatment principle (NT) GATT 1994. It shows that while the non-discrimination principles are meant to promote trade liberalisation and economic growth, they produce the opposite effect in developing and least developed countries like ECOWAS and aggravate the tension between those countries and the WTO. It argues that the MFN is used to deny market access to the developing countries by exposing them to stiff but unequal competitive conditions and the NT to deny national governments the policy space to protect and promote national industries, employment and economic growth. It challenges the general assumption that the MFN and the NT are good and in the interest of all the WTO Members and rather identifies them as lynch-pins of economic development in the ECOWAS region. It also shows, contrary to the assumption of non-participation, how the ECOWAS High Contracting Parties are adapting their trading systems and harmonising their laws to the key provisions of Articles I and III of the GATT. It shows that the principles of non-discrimination are the outcome of the standard-setting procedures legally formulated as the SPS and TBT Agreements which favour the developed countries and how the Dispute Settlement Body has rejected the ‘aims-and-effect’ approach, taken a literal approach, overly emphasising trade liberalisation to the neglect of market access and economic development. This dissertation concludes that it is pre-mature for ECOWAS to assume Articles I and III obligations and recommends using the provisions of Article XXIV to build up effective influence through regional organisations and incrementally uniting to transform the GATT.This study is funded by the Brunel Law School
Keywords: ECOWAS; GATT; Tension; WTO; World Trade Organisation

Essays in corporate restructuring, reputation and law - Polo, Andrea (Oxford University, 2012)
This dissertation consists of three essays which examine topics at the intersection of law and finance. The first essay investigates the role of regulatory sanctions and reputational damage in financial markets. We study the impact of the announcement of enforcement of financial and securities regulation by the UK’s financial regulators on the market price of penalized firms. We find that reputational sanctions are very real: their stock price impact is on average almost 9 times larger than the financial penalties imposed. Furthermore, reputational losses are confined to misconduct that directly affects parties who trade with the firm (such as customers and investors). In the second essay we analyze the costs and benefits associated with secured creditor control in bankruptcy. We do it by studying the highly contested practice of UK pre-packs, where a deal to sell the business is agreed before publicly entering into bankruptcy. Contrary to widespread criticism that this procedure leads to collusion, we find no evidence of exploitation of conflict of interests and we find that it preserves the value of the business and maximizes recovery in circumstances in which a public announcement of bankruptcy would destroy value. In small businesses where secured creditors are concentrated the benefits of their control seem to outweigh the costs. Finally, in the last essay we examine whether mandatory shareholder voting prevents wealth destruction in corporate acquisitions. We study the UK setting where all large transactions must have shareholder approval. We observe that such Class 1 transactions always get consent. Nevertheless, there is a striking difference between the performance of acquirers between Class 1 and other transactions. The finding is most pronounced for transactions in a narrow neighbourhood of the size threshold, and is robust to a large set of controls for confounding effects.

Public assets financing in Nigeria : the imperatives for legal reforms to unlock domestic financial resources and foreign capital for infrastructure development - Soyeju, Olufemi Olugbemiga (University of Pretoria, 2012)
Infrastructure is one of the main parameters of economic growth and a country‘s competitiveness depends on the provision and maintenance of efficient and productive infrastructure assets. However, Nigeria, like most countries in Sub-Saharan Africa has the lowest quantity and poorest quality of stocks of infrastructure assets in the world and this phenomenally poor infrastructure has remained an impediment to development in the country. Decades of sub-optimal investment, poor maintenance culture and the fact that the required infrastructure investments could not be accommodated within the available fiscal space as a result of budgetary constraints have all contributed to the Nigeria‘s infrastructure deficit. The immediate outcome of this however is that the available infrastructure assets across the Nigerian landscape are in decrepit state and absurdly inadequate. Besides, the present demand for basic infrastructure services has grown astronomically out-stripping the supply capacity of the existing ones. Closing the infrastructure financing gap will however require increased investment by private investors through creative financing in an enabling legal and financial environment. Outside the budgetary constraints, the absence of efficient maintenance and management of infrastructure assets and quality service delivery by the public sector are some of the reasons why procurement of public infrastructure stocks by government through the traditional approach is no longer plausible and hence, the general appeal of the public-private partnership framework. However, despite all the potentials, the public private partnership technique in Nigeria has not made an appreciable impact in closing the infrastructure gaps due to lack of access to long-term financing. It is against this back-drop that this study has sought to investigate how reforms of the legal and financial infrastructure could widen access to financing through innovative financial resource mobilization in scaling-up infrastructure development and service delivery to the teeming Nigeria population. Therefore, the central thesis of this study is that the inadequacy of appropriate laws and inefficient financial system are partly responsible for the huge financing gaps in the Nigeria‘s infrastructure market and with the legal and financial reforms, an enabling legal and financial environment that would open up space for resource mobilization through innovative financing techniques and sources will be created thereby widening access to long-term financing and increasing the appetite for private investment in the nation‘s public infrastructure assets and services. So, the overarching objective of this thesis is to explore how legal and financial system reforms can facilitate the development of financial models and instruments that can help mobilize financial resources to fund infrastructure and bridge the huge infrastructure financing gaps in Nigeria in a sustainable fashion. Given the infrastructure poverty that constrains economic growth and development in Nigeria, the outcomes of this proposed study would help inform the need for the legal and financial system reforms to unlock resources in addressing the problems of financing gaps in infrastructure projects development in Nigeria. Besides, such outcomes based on the Nigerian experience in infrastructure financing and development may be turned into valuable knowledge for policy –making and further research in Nigeria. Copyright
Keywords: Foreign capital; Infrastructure; Legal reform; Nigeria; Public assets

Understanding fiduciary duties: conflict of interest and proper exercise of judgment in private law - Valsan, Remus (McGill University, 2012)
This dissertation analyses the content and justification of the notion of fiduciary duties in private law relations. The thesis promotes the following understanding of fiduciary duties: in a legal relation where one party undertakes to act in the interests of another, and acquires decision-making authority over the other's interests, such party undertakes a core duty to exercise his best judgement in the other's interests. The core judgement duty requires a fiduciary to exercise judgement based on relevant considerations. While what constitutes a relevant consideration can be determined objectively, the weight to be ascribed to each relevant factor is left at the fiduciary's subjective appreciation.Due to the existence of this core duty, the law imposes a set of proscriptive duties. The proscriptive duties require a fiduciary to manage situations of conflict of interest. Their purpose is prophylactic: they aim to prevent self-interest (or another duty to exercise proper judgement) from affecting the reliability of fiduciary's judgement in a conscious or subconscious way. The proscriptive duties protect the core duty to exercise judgement and, as a result, the beneficiary's right to a proper exercise of judgement by the fiduciary.
Keywords: Conflict of interest; Fiduciary duties; Judgment; Private law

Corporate Governance and the Relationship between Default Risk and the Earning Response Coefficient - Zakaria, Nor Balkish (Victoria University of Wellington, 2012)
This study examines the effect of corporate governance on the relationship between default risk and the earnings response coefficient (ERC). Using a sample of 2,004 firm-years comprising 334 firms listed on the Bursa Malaysia over a six year period from 2002 to 2007, this study tests whether corporate governance mitigates the effect of default risk on ERC while controlling for the established determinants of ERC — beta, growth, earnings persistence and size. Using reverse regression, the study confirms that beta is negatively related to ERC and that growth, earnings persistence and size are positively related to ERC. Default risk is found to be negatively related to ERC thus confirming that beta is only a partial measure of risk relevant to ERC. Corporate governance — as indicated by audit quality, audit committee expertise and independence, and board independence and board shareholding — mitigates the negative effect of default risk on ERC. The results of the study hold both for the pooled sample of 2,004 firm-year observations and on a year by year basis for the 334 firms in the sample. The results are also found to be robust to various sensitivity tests including to alternative measures of the variables. The study thus provides systematic and comprehensive additional evidence on the determinants of ERC. Of itself this is an important contribution to the literature but especially so given that the evidence comes from Malaysia — an emerging economy — whereas the existing empirical literature relates mainly to developed countries.
Keywords: Corporate governance; Default risk; Earnings response coefficient